A natural graphite composite negative electrode material and preparation method thereof and lithium ion battery
By building a three-dimensional conductive network on the surface of natural graphite and doping metal particles, the problem of uneven coating of existing natural graphite composites is solved, and its conductivity and electrochemical cycling performance are significantly improved, achieving a more stable structure and a longer cycle life.
Patent Information
- Application Number
- CN202411856618.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The existing natural graphite composite anode materials have problems of uneven coating in surface modification treatment, which affects their electrical conductivity and electrochemical cycling properties, and are difficult to achieve commercial application.
By constructing a three-dimensional conductive network on the surface of natural graphite, magnesium ions and aluminum ions are uniformly dispersed in the fluffy mesh three-dimensional carbon network, and copper and silver metal particles are doped in the amorphous carbon cladding layer to form a uniform carbon cladding layer.
The conductivity and electrochemical cycling performance of natural graphite composite negative electrode materials have been significantly improved, the structural stability and cycle life of the material have been enhanced, and the occurrence of electrochemical side reactions has been reduced.
Smart Images

Figure CN119315018B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a natural graphite composite negative electrode material and a preparation method thereof and a lithium ion battery, belonging to the technical field of materials, in particular to the technical field of electrode materials. Background Art
[0002] Lithium-ion battery anode materials are an important component of lithium-ion batteries, and they play a role in storing and releasing energy during the cycle of lithium-ion batteries. Among them, the widely used graphite anode materials generally have many surface defects and solvent co-embedding leading to material structure collapse. Therefore, they need to be surface modified to stabilize the material structure and improve performance.
[0003] For example, CN111354513A discloses a silver-doped polypyrrole-coated graphite composite material and a preparation method thereof, wherein silver nitrate is used as an oxidant to promote the in-situ polymerization of pyrrole monomers, and silver nitrate is reduced to silver element and doped in polypyrrole to obtain a core-shell type silver-doped polypyrrole-coated graphite composite material, which effectively improves the conductivity of the material. Although the preparation method meets the requirements of environmental protection and greenness, there is a problem of uneven coating of silver-doped polypyrrole on the surface of natural spherical graphite, which is not conducive to the commercial application of natural graphite.
[0004] Therefore, providing a new type of natural graphite composite negative electrode material and a preparation method thereof and a lithium ion battery has become a technical problem that urgently needs to be solved in this field. Summary of the invention
[0005] In order to solve the above shortcomings and deficiencies, the purpose of the present invention is to provide a natural graphite composite negative electrode material and a preparation method thereof and a lithium ion battery. The natural graphite composite negative electrode material provided by the present invention has a three-dimensional conductive network and is doped with metal, has good conductivity and excellent electrochemical cycle performance.
[0006] In order to achieve the above objectives, on the one hand, the present invention provides a natural graphite composite negative electrode material, wherein the natural graphite composite negative electrode material includes natural graphite, a fluffy mesh three-dimensional carbon network coated on the outside of the natural graphite, and an amorphous carbon coating layer arranged outside the fluffy mesh three-dimensional carbon network; wherein magnesium ions and / or aluminum ions are dispersed in the fluffy mesh three-dimensional carbon network, and the amorphous carbon coating layer is doped with copper particles and / or silver particles.
[0007] In the natural graphite composite negative electrode material described above, magnesium ions and / or aluminum ions are uniformly dispersed in the fluffy three-dimensional carbon network, and copper particles and / or silver particles are uniformly doped in the amorphous carbon coating layer. The copper particles and silver particles refer to single substances of copper and silver.
[0008] As a specific embodiment of the above-mentioned natural graphite composite negative electrode material of the present invention, the natural graphite is natural spherical graphite or the like.
[0009] On the other hand, the present invention also provides a method for preparing the above-mentioned natural graphite composite negative electrode material, wherein the preparation method comprises:
[0010] Step (1): uniformly dispersing pyrrole monomer, copper nitrate and / or silver nitrate, magnesium trifluoromethanesulfonate and / or aluminum trifluoromethanesulfonate and sodium alginate in a solvent to obtain a pyrrole monomer solution, a copper nitrate and / or silver nitrate solution, a magnesium trifluoromethanesulfonate and / or aluminum trifluoromethanesulfonate solution and a sodium alginate solution;
[0011] Step (2): adding natural graphite to a solution of magnesium trifluoromethanesulfonate and / or aluminum trifluoromethanesulfonate and mixing the mixture evenly, wherein the mixture is acidic;
[0012] Step (3): adding the sodium alginate solution to the mixture obtained in step (2), and at 20-30° C. (preferably room temperature) under stirring and acidic conditions, the magnesium ions and / or aluminum ions in the solution replace the sodium ions in the sodium alginate through a replacement reaction to form and precipitate a hydrogel of magnesium alginate and / or aluminum alginate;
[0013] Step (4): adding a solution of copper nitrate and / or silver nitrate to the mixture obtained in step (3) and mixing the mixture evenly;
[0014] Step (5): adding the pyrrole monomer solution to the mixture obtained in step (4), reacting under stirring and constant temperature conditions, and aging the product after the reaction is completed;
[0015] Step (6): The product after the aging treatment is washed, filtered, dried and carbonized in sequence to obtain the natural graphite composite negative electrode material.
[0016] As a specific embodiment of the preparation method described above of the present invention, the mass ratio of natural graphite powder, pyrrole monomer, copper nitrate and / or silver nitrate, sodium alginate and magnesium trifluoromethanesulfonate and / or aluminum trifluoromethanesulfonate is 1000:5~80:30~100:0.00001~50:0.001~50.
[0017] As a specific embodiment of the preparation method described above of the present invention, in step (1), in the pyrrole monomer solution, the concentration of pyrrole monomer is 0.1-1.5 mol / L; in the solution of copper nitrate and / or silver nitrate, the concentration of copper nitrate and / or silver nitrate is 0.05-1.9 mol / L, preferably only copper nitrate is used, and more preferably, the concentration of copper nitrate is 0.05-1.5 mol / L; in the solution of magnesium trifluoromethanesulfonate and / or aluminum trifluoromethanesulfonate, the concentration of magnesium trifluoromethanesulfonate and / or aluminum trifluoromethanesulfonate is 0.0001-5 mol / L, preferably only aluminum trifluoromethanesulfonate is used, and more preferably, the concentration of aluminum trifluoromethanesulfonate is 0.0001-0.2 mol / L; in the sodium alginate solution, the concentration of sodium alginate is 0.001-1 mol / L.
[0018] The present invention does not make specific requirements on the purity of raw materials such as copper nitrate and / or silver nitrate, pyrrole monomer, magnesium trifluoromethanesulfonate and / or aluminum trifluoromethanesulfonate and sodium alginate used in the preparation method described above, and can be reasonably selected as needed. Under the premise of being available, raw materials with higher purity should be selected as much as possible. For example, in some embodiments of the present invention, the purity of copper nitrate and silver nitrate is more than 95%, the purity of pyrrole monomer is greater than 95%, the purity of these two trifluoromethanesulfonates of magnesium trifluoromethanesulfonate and aluminum trifluoromethanesulfonate is more than 88%, and the purity of sodium alginate is more than 90%.
[0019] As a specific embodiment of the preparation method described above of the present invention, in step (1), the solvent includes deionized water and / or an organic solvent.
[0020] As a specific implementation of the above preparation method of the present invention, in step (2), the pH value of the system is 1-5.
[0021] In the steps (2) to (5) of the preparation method described above, uniform mixing can be achieved by stirring or the like, and preferably, the stirring can be uniform stirring. In some embodiments of the present invention, the uniform stirring speed in steps (2), (3), (4) and (5) can be 200-1000 rpm; and the temperature of the stirring process can be reasonably adjusted as needed. For example, in some embodiments of the present invention, step (4) can be stirred at room temperature.
[0022] As a specific implementation of the above preparation method of the present invention, in step (3), the replacement reaction time is 2 to 5 hours.
[0023] The insoluble matter precipitated in step (3) of the preparation method described above of the present invention, i.e., the hydrogel of magnesium alginate and / or aluminum alginate, is further subjected to carbonization treatment to form a fluffy three-dimensional carbon network coated on the outside of the natural graphite; the polypyrrole formed by in-situ polymerization of pyrrole monomers in step (5) is further subjected to carbonization treatment to form an amorphous carbon coating layer coated on the outside of the fluffy three-dimensional carbon network.
[0024] As a specific embodiment of the preparation method described above of the present invention, in step (5), the reaction temperature is from room temperature to 60° C., and the reaction time is 2 to 5 hours;
[0025] And / or the aging is aging from room temperature to 60° C. for not less than 12 hours.
[0026] In step (5) of the preparation method described above, the pyrrole monomer solution is added to the mixture obtained in step (4), and under the conditions of stirring, acidic system and constant temperature, the pyrrole monomer undergoes oxidative polymerization, accompanied by the reduction of copper ions and / or silver ions.
[0027] In step (6) of the preparation method described above, the cleaning is performed by using deionized water for multiple cleanings until the pH value of the cleaning solution is 6-7.
[0028] As a specific embodiment of the preparation method described above of the present invention, in step (6), the drying is performed at 60-120° C. for 12-24 hours;
[0029] And / or the temperature of the carbonization treatment is 800-1500°C.
[0030] Compared with the conventional solid-phase method for preparing the same type of natural graphite composite negative electrode material, the liquid-phase method for preparing the natural graphite composite negative electrode material in the present invention can make the carbon coating layer on the surface of the natural graphite more uniform, reduce the exposure of the surface active sites, and when the natural graphite composite negative electrode material is used in a lithium-ion battery, there are fewer electrochemical side reactions.
[0031] In yet another aspect, the present invention further provides a lithium ion battery, wherein the negative electrode material of the lithium ion battery is the natural graphite composite negative electrode material described above.
[0032] Compared with the prior art, the technical solution provided by the present invention can achieve at least the following beneficial technical effects:
[0033] The natural graphite composite negative electrode material provided by the present invention comprises natural graphite, a fluffy mesh three-dimensional carbon network coated on the outside of the natural graphite, and an amorphous carbon coating layer arranged outside the fluffy mesh three-dimensional (stereoscopic) carbon network; wherein magnesium ions and / or aluminum ions are dispersed in the fluffy mesh three-dimensional carbon network, and copper and / or silver metal particles are doped in the amorphous carbon coating layer. The fluffy mesh three-dimensional carbon network is formed by carbonizing the insoluble matter precipitated during the preparation process, i.e., the hydrogel of magnesium alginate and / or aluminum alginate, and the insoluble matter is formed by the metal ions (Mg 2+ and / or Al 3+ ) is formed by replacing the sodium ions in the doped sodium alginate, and the amorphous carbon coating layer is formed by carbonizing the polypyrrole formed by the in-situ polymerization of the pyrrole monomer.
[0034] The metal doped in the natural graphite composite negative electrode material can improve the conductivity of the natural graphite composite negative electrode material. When magnesium ions and / or aluminum ions are dispersed in the fluffy mesh three-dimensional carbon network and copper and / or silver metal particles are doped in the amorphous carbon coating layer, a three-dimensional conductive network can be formed on the surface of the natural graphite, which can improve the conductivity and effectively increase the diffusion channel of lithium ions.
[0035] The fluffy (soft) mesh-like three-dimensional carbon network in the natural graphite composite negative electrode material can effectively alleviate the volume change of natural graphite during the charge and discharge process. The amorphous carbon coating layer can reduce the defect concentration on the surface of the composite electrode material and prevent the co-embedding of solvent ions. The synergistic effect of the two can improve the structural stability of the natural graphite composite negative electrode material, and can effectively improve the specific capacity and cycle life of the natural graphite composite negative electrode material.
[0036] In summary, the natural graphite composite negative electrode material provided by the present invention has more excellent electrochemical cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0038] Figure 1a and Figure 1b This is a scanning electron microscope image of the natural spherical graphite composite negative electrode material provided in Example 1 of the present invention, and the Mag of the two are 0.5K and 1.5K respectively.
[0039] Figure 1c and Figure 1dThis is a scanning electron microscope image of the natural spherical graphite composite negative electrode material provided in Example 2 of the present invention, and the Mag of the two are 0.5K and 1.5K respectively.
[0040] Figure 1e and Figure 1f This is a scanning electron microscope image of the natural spherical graphite composite negative electrode material provided in Example 3 of the present invention, and the Mag of the two are 0.5K and 1.5K respectively.
[0041] Figure 1g and Figure 1h Element distribution diagrams of natural spherical graphite negative electrode materials provided in Example 1 of the present invention and Comparative Example 1, respectively.
[0042] Figure 2 1C / 1C electrochemical performance cycle diagram of the natural spherical graphite negative electrode material provided in Examples 1 to 3 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0043] It should be noted that the term "comprises" and any variations thereof in the specification and claims of the present invention and the above-mentioned drawings are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0044] "Scope" disclosed in the present invention is given in the form of lower limit and upper limit. It can be one or more lower limits, and one or more upper limits respectively. A given range is defined by selecting a lower limit and an upper limit. The selected lower limit and upper limit define the boundaries of a particular range. All ranges defined in this way are combinable, i.e. any lower limit can be combined with any upper limit to form a range. For example, for a specific parameter, a range of 60-120 and 80-110 is listed, and it is understood that a range of 60-110 and 80-120 is also expected. In addition, if the minimum range values listed are 1 and 2, and the maximum range values listed are 3, 4 and 5, then the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5.
[0045] In the present invention, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" have been listed in the present invention, and "0-5" is just an abbreviation of these numerical combinations.
[0046] In the present invention, unless otherwise specified, all embodiments and preferred embodiments mentioned in the present invention can be combined with each other to form a new technical solution.
[0047] In the present invention, unless otherwise specified, all technical features and preferred features mentioned in the present invention can be combined with each other to form a new technical solution.
[0048] In the present invention, unless otherwise specified, all steps mentioned herein may be performed sequentially or randomly, but are preferably performed sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0049] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and Examples. The following described embodiments are some embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0050] Example 1
[0051] This embodiment provides a natural spherical graphite composite negative electrode material, which is prepared by a preparation method comprising the following specific steps:
[0052] Step (1): uniformly dispersing pyrrole monomer, copper nitrate, magnesium trifluoromethanesulfonate and sodium alginate in water respectively to obtain pyrrole monomer solution, copper nitrate solution, magnesium trifluoromethanesulfonate solution and sodium alginate solution, wherein the concentration of pyrrole monomer in the pyrrole monomer solution is 0.1 mol / L, the concentration of copper nitrate in the copper nitrate solution is 0.1 mol / L, the concentration of magnesium trifluoromethanesulfonate in the magnesium trifluoromethanesulfonate solution is 0.005 mol / L, and the concentration of sodium alginate in the sodium alginate solution is 0.05 mol / L, and the mass ratio of natural graphite powder, pyrrole monomer, copper nitrate, sodium alginate and magnesium trifluoromethanesulfonate is 1000:20:40:0.05:0.005;
[0053] Step (2): adding 1 kg of natural spherical graphite powder to the magnesium trifluoromethanesulfonate solution and stirring at room temperature to mix evenly, ensuring that the pH value of the system is 2.5;
[0054] Step (3): adding the sodium alginate solution to the mixture obtained in step (3), maintaining uniform stirring at room temperature at a speed of 600 rpm. Under acidic conditions, the magnesium ions in the solution replace the sodium ions in the sodium alginate through a replacement reaction to form and precipitate insoluble matter, i.e., a hydrogel of magnesium alginate;
[0055] Wherein, the time of the replacement reaction can be 3h;
[0056] Step (4): adding the copper nitrate solution to the mixture obtained in step (3), and stirring at room temperature to uniformly mix the system;
[0057] Step (5): adding the pyrrole monomer solution to the mixture obtained in step (4), maintaining the temperature at room temperature and stirring at a speed of 600 rpm during the experiment, reacting under this condition for 2 hours, and aging the product at 60° C. for 24 hours after the reaction;
[0058] Step (6): The aged product is washed, filtered, dried and carbonized, wherein the washing process uses deionized water for multiple washings until the pH value of the last washing solution is 7, the product is dried at 80°C for 24 hours, and the calcination temperature is 850°C, and finally a black powder material is obtained, which is the natural spherical graphite composite negative electrode material.
[0059] Example 2
[0060] This embodiment provides a natural spherical graphite composite negative electrode material, which is prepared by a preparation method comprising the following specific steps:
[0061] Step (1): uniformly dispersing pyrrole monomer, copper nitrate, magnesium trifluoromethanesulfonate and sodium alginate in water respectively to obtain pyrrole monomer solution, copper nitrate solution, magnesium trifluoromethanesulfonate solution and sodium alginate solution, wherein the concentration of pyrrole monomer in the pyrrole monomer solution is 0.1 mol / L, the concentration of copper nitrate in the copper nitrate solution is 0.1 mol / L, the concentration of magnesium trifluoromethanesulfonate in the magnesium trifluoromethanesulfonate solution is 0.005 mol / L, and the concentration of sodium alginate in the sodium alginate solution is 0.05 mol / L, and the mass ratio of natural graphite powder, pyrrole monomer, copper nitrate, sodium alginate and magnesium trifluoromethanesulfonate is 1000:20:40:0.05:0.0034;
[0062] Step (2): adding 1 kg of natural spherical graphite powder to the magnesium trifluoromethanesulfonate solution and stirring at room temperature to mix the mixture evenly, ensuring that the pH value of the system is 4;
[0063] Step (3): adding the sodium alginate solution to the mixture obtained in step (3), maintaining uniform stirring at room temperature at a speed of 600 rpm. Under acidic conditions, the magnesium ions in the solution replace the sodium ions in the sodium alginate through a replacement reaction to form and precipitate insoluble matter, i.e., a hydrogel of magnesium alginate;
[0064] Wherein, the time of the replacement reaction can be 3h;
[0065] Step (4): adding the copper nitrate solution to the mixture obtained in step (3), and stirring at room temperature to uniformly mix the system;
[0066] Step (5): adding the pyrrole monomer solution to the mixture obtained in step (4), maintaining the temperature at room temperature and stirring at a speed of 600 rpm during the experiment, reacting under this condition for 2 hours, and aging the product at 60° C. for 24 hours after the reaction;
[0067] Step (6): The aged product is washed, filtered, dried and carbonized, wherein the washing process uses deionized water for multiple washings until the pH value of the last washing solution is 7, the product is dried at 80°C for 24 hours, and the calcination temperature is 850°C, and finally a black powder material is obtained, which is the natural spherical graphite composite negative electrode material.
[0068] Example 3
[0069] This embodiment provides a natural spherical graphite composite negative electrode material, which is prepared by a preparation method comprising the following specific steps:
[0070] Step (1): uniformly dispersing pyrrole monomer, copper nitrate, aluminum trifluoromethanesulfonate and sodium alginate in water respectively to obtain pyrrole monomer solution, copper nitrate solution, aluminum trifluoromethanesulfonate solution and sodium alginate solution, wherein the concentration of pyrrole monomer in the pyrrole monomer solution is 0.1 mol / L, the concentration of copper nitrate in the copper nitrate solution is 0.1 mol / L, the concentration of aluminum trifluoromethanesulfonate in the aluminum trifluoromethanesulfonate solution is 0.005 mol / L, and the concentration of sodium alginate in the sodium alginate solution is 0.05 mol / L, and the mass ratio of natural graphite powder, pyrrole monomer, copper nitrate, sodium alginate and aluminum trifluoromethanesulfonate is 1000:20:40:0.05:0.0033;
[0071] Step (2): adding 1 kg of natural spherical graphite powder to the aluminum trifluoromethanesulfonate solution and stirring at room temperature to mix the mixture evenly, ensuring that the pH value of the system is 2.5;
[0072] Step (3): adding the sodium alginate solution to the mixture obtained in step (3), and stirring at a constant speed of 600 rpm at room temperature. Under acidic conditions, the aluminum ions in the solution replace the sodium ions in the sodium alginate through a replacement reaction to form and precipitate insoluble matter, i.e., aluminum alginate hydrogel;
[0073] Wherein, the time of the replacement reaction can be 3h;
[0074] Step (4): adding the copper nitrate solution to the mixture obtained in step (3), and stirring at room temperature to uniformly mix the system;
[0075] Step (5): adding the pyrrole monomer solution to the mixture obtained in step (4), maintaining the temperature at room temperature and stirring at a speed of 600 rpm during the experiment, reacting under this condition for 2 hours, and aging the product at 60° C. for 24 hours after the reaction;
[0076] Step (6): The aged product is washed, filtered, dried and carbonized, wherein the washing process uses deionized water for multiple washings until the pH value of the last washing solution is 7, the product is dried at 80°C for 24 hours, and the calcination temperature is 850°C, and finally a black powder material is obtained, which is the natural spherical graphite composite negative electrode material.
[0077] Comparative Example 1
[0078] This comparative example provides a natural spherical graphite composite negative electrode material, and the preparation method thereof is different from that of Example 1 only in that this comparative example does not use metal ion replacement doped alginate hydrogel to coat the natural spherical graphite negative electrode material, and the natural spherical graphite composite negative electrode material is prepared by a preparation method comprising the following specific steps:
[0079] Step (1): uniformly dispersing pyrrole monomer, copper nitrate and magnesium trifluoromethanesulfonate in water respectively to obtain pyrrole monomer solution, copper nitrate solution and magnesium trifluoromethanesulfonate solution, wherein the concentration of pyrrole monomer in the pyrrole monomer solution is 0.1 mol / L, the concentration of copper nitrate in the copper nitrate solution is 0.1 mol / L, and the concentration of magnesium trifluoromethanesulfonate in the magnesium trifluoromethanesulfonate solution is 0.005 mol / L, and the mass ratio of natural graphite powder, pyrrole monomer, copper nitrate and magnesium trifluoromethanesulfonate is ensured to be 1000:20:40:0.005;
[0080] Step (2): adding 1 kg of natural spherical graphite powder to the magnesium trifluoromethanesulfonate solution and stirring at room temperature to mix evenly, ensuring that the pH value of the system is 2.5;
[0081] Step (3): adding the copper nitrate solution to the mixture obtained in step (2), and stirring at room temperature to uniformly mix the system;
[0082] Step (4): adding the pyrrole monomer solution to the mixture obtained in step (3), maintaining the temperature at room temperature and stirring at a speed of 600 rpm during the experiment, reacting under this condition for 2 hours, and aging the product at 60° C. for 24 hours after the reaction;
[0083] Step (5): The aged product is washed, filtered, dried and carbonized, wherein the washing process uses deionized water for multiple washings until the pH value of the last washing solution is 7, the product is dried at 80°C for 24 hours, and the calcination temperature is 850°C, and finally a black powder material is obtained, which is the natural spherical graphite composite negative electrode material.
[0084] Test Example 1
[0085] In this test example, a Hitachi S-4800 scanning electron microscope was used to perform field emission scanning electron microscope analysis on the natural graphite composite negative electrode materials provided in Examples 1 to 3 of the present invention under conventional test conditions. The obtained scanning electron microscope images and the element distribution maps obtained by SEM+mapping are shown in FIG. Figure 1a-1h shown.
[0086] from Figure 1a-1f It can be seen that the natural graphite composite negative electrode material particles provided in Examples 1 to 3 of the present invention are quasi-circular, with a relatively smooth surface and no obvious damage.
[0087] from Figure 1g-1h It can be seen that compared with the natural graphite composite negative electrode material provided in Comparative Example 1, the natural graphite composite negative electrode material particles provided in Example 1 of the present invention have magnesium ions uniformly dispersed on the surface, and substantially no sodium ions (specifically, Figure 1g As shown in Figure 2, it is proved that under acidic conditions, magnesium ions do replace sodium ions in sodium alginate to form magnesium alginate hydrogel, which forms a fluffy three-dimensional carbon network after carbonization. Figure 1g-1h It can also be seen that copper is dispersed on the surface of the natural graphite composite negative electrode material particles provided in Example 1 of the present invention and Comparative Example 1, indicating that copper is indeed doped into the amorphous carbon coating layer.
[0088] Test Example 2
[0089] This test example also tests the electrochemical performance of the natural graphite composite negative electrode materials provided in each embodiment and comparative example, including the following specific steps:
[0090] Step 1): The natural graphite composite negative electrode material provided in each embodiment and comparative example is used as the negative electrode active material, and the three are mixed evenly according to the mass ratio of negative electrode active material: LA133: SuperP = 94:3:3, and then coated on the copper foil current collector, and then dried, cut, and rolled to obtain a negative electrode sheet.
[0091] Step 2): Assemble the negative electrode sheets obtained above into 2025 button cells and perform the first charge capacity and first week coulomb efficiency tests, wherein the counter electrode is a lithium sheet, the solute of the electrolyte is LiPF6, the solvent is a mixture of DEC, DMC and EC in a volume ratio of 1:1:1, the concentration of LiPF6 is 1 mol / L, the diaphragm is commercially available Celgard2320, the test is performed on a battery tester CT300A1U, the charge and discharge voltage is 0.005-1.5V, deep discharge (0.1C-0.01C) and 0.1C charge are performed in the first week, and the electrochemical performance is as follows Figure 2 And as shown in Table 1.
[0092] Table 1
[0093]
[0094] from Figure 2 As can be seen from Table 1, compared with the natural graphite composite negative electrode material provided in Comparative Example 1, the natural graphite composite negative electrode materials provided in Examples 1 to 3 of the present invention all show better cycle performance, especially after 100 cycles, the natural graphite composite negative electrode material provided in Comparative Example 1 shows obvious capacity decay, while the capacity fluctuation of the natural graphite composite negative electrode material provided in Examples 1 to 3 of the present invention is small, and its first-week discharge specific capacity is basically above 400 mAh / g, and the first-week coulomb efficiency is higher than 91%. The above experimental results are sufficient to prove that the natural graphite composite negative electrode material provided in the embodiment of the present invention has excellent structural stability and electrochemical cycle performance.
[0095] The above is only a specific embodiment of the present invention, and cannot be used to limit the scope of the invention. Therefore, the replacement of equivalent components, or equivalent changes and modifications made according to the protection scope of the patent of the present invention, should still fall within the scope of this patent. In addition, the technical features of the present invention can be freely combined with each other, with each other and with each other, and with each other.
Claims
1. A natural graphite composite negative electrode material, characterized in that: The natural graphite composite negative electrode material includes natural graphite, a fluffy mesh three-dimensional carbon network coated on the outside of the natural graphite, and an amorphous carbon coating layer arranged outside the fluffy mesh three-dimensional carbon network; wherein magnesium ions and / or aluminum ions are dispersed in the fluffy mesh three-dimensional carbon network, and copper particles and / or silver particles are doped in the amorphous carbon coating layer.
2. The natural graphite composite negative electrode material according to claim 1, characterized in that: The natural graphite is natural spherical graphite.
3. The method for preparing the natural graphite composite negative electrode material according to claim 1 or 2, characterized in that: The preparation method comprises: Step (1): uniformly dispersing pyrrole monomer, copper nitrate and / or silver nitrate, magnesium trifluoromethanesulfonate and / or aluminum trifluoromethanesulfonate and sodium alginate in a solvent to obtain a pyrrole monomer solution, a copper nitrate and / or silver nitrate solution, a magnesium trifluoromethanesulfonate and / or aluminum trifluoromethanesulfonate solution and a sodium alginate solution; Step (2): adding natural graphite to a solution of magnesium trifluoromethanesulfonate and / or aluminum trifluoromethanesulfonate and mixing the mixture evenly, wherein the system is acidic; Step (3): adding the sodium alginate solution to the mixture obtained in step (2), and at 20-30° C., stirring and under acidic conditions, the magnesium ions and / or aluminum ions in the solution replace the sodium ions in the sodium alginate through a replacement reaction to form and precipitate a hydrogel of magnesium alginate and / or aluminum alginate; Step (4): adding a solution of copper nitrate and / or silver nitrate to the mixture obtained in step (3) and mixing the mixture evenly; Step (5): adding the pyrrole monomer solution to the mixture obtained in step (4), reacting under stirring and constant temperature conditions, and aging the product after the reaction is completed; Step (6): The product after the aging treatment is washed, filtered, dried and carbonized in sequence to obtain the natural graphite composite negative electrode material.
4. The preparation method according to claim 3, characterized in that: The mass ratio of natural graphite powder, pyrrole monomer, copper nitrate and / or silver nitrate, sodium alginate and magnesium trifluoromethanesulfonate and / or aluminum trifluoromethanesulfonate is 1000:5-80:30-100:0.00001-50:0.001-50.
5. The preparation method according to claim 3 or 4, characterized in that: In step (1), in the pyrrole monomer solution, the concentration of pyrrole monomer is 0.1-1.5 mol / L, in the solution of copper nitrate and / or silver nitrate, the concentration of copper nitrate and / or silver nitrate is 0.05-1.9 mol / L, in the sodium alginate solution, the concentration of sodium alginate is 0.001-1 mol / L, and in the solution of magnesium trifluoromethanesulfonate and / or aluminum trifluoromethanesulfonate, the concentration of magnesium trifluoromethanesulfonate and / or aluminum trifluoromethanesulfonate is 0.0001-5 mol / L.
6. The preparation method according to claim 3 or 4, characterized in that: In step (1), pyrrole monomer, copper nitrate and / or silver nitrate, and magnesium trifluoromethanesulfonate and / or aluminum trifluoromethanesulfonate are uniformly dispersed in a solvent to obtain a pyrrole monomer solution, a copper nitrate and / or silver nitrate solution, and a magnesium trifluoromethanesulfonate and / or aluminum trifluoromethanesulfonate solution; wherein the solvent comprises deionized water and / or an organic solvent; The sodium alginate is uniformly dispersed in deionized water to obtain a sodium alginate solution.
7. The preparation method according to claim 3 or 4, characterized in that: In step (2), the pH value of the system is 1-5.
8. The preparation method according to claim 3 or 4, characterized in that: In step (3), the replacement reaction time is 2 to 5 hours.
9. The preparation method according to claim 3 or 4, characterized in that: In step (5), the reaction temperature is from room temperature to 60°C, and the reaction time is 2 to 5 hours; And / or the aging is aging from room temperature to 60° C. for not less than 12 hours.
10. The preparation method according to claim 3 or 4, characterized in that: In step (6), the drying is performed at 60-120° C. for 12-24 hours; And / or the temperature of the carbonization treatment is 800-1500°C.
11. A lithium ion battery, characterized in that: The negative electrode material of the lithium ion battery is the natural graphite composite negative electrode material according to claim 1 or 2.
Citation Information
Patent Citations
Silver-doped polypyrrole coated graphite composite material and preparation method thereof
CN111354513A
Method for preparing alginate for fast preparation of hydrogel
CN101423564A
Graphene coated graphite composite lithium ion battery negative material and its preparation method
CN104332616A